Welfare Comparison under Exact Aggregation - Jorgenson, Dale W.; Lau, Lawrence J.; Stoker, Thomas M. (American Economic Review, 2016)
new econometric model of aggregate consumer behavior in the United States and to apply this model to the analysis of impacts of alternative economic policies on the welfare of individual consuming units. The model incorporates time-series data on quantities consumed, prices, the level and distribution of income, and demographic characteristics of the population. It also incorporates cross-section data on the allocation of consumer expenditures for households with different demographic characteristics. Our econometric model is based on the theory of exact aggregation developed by Lau (1977a, c). This theory makes it possible to dispense with the notion of a representative consumer in constructing models of aggregate consumer behavior. One of the most remarkable implications of Lau's theory of exact aggregation is that systems of demand functions for individuals with common demographic characteristics can be recovered uniquely from the system of aggregate demand functions. Using the individual demand functions we can analyze the impact of economic policy on consumer welfare.